Evans, John S. - (:unkn) unknown (My University, 2026)
Dr. Evans' research focuses on risk assessment, uncertainty analysis, and decision making in environmental health. His early work concentrated on improving the models used to estimate the health impacts of accidental releases of radionuclides from nuclear power plants and on understanding the evidence from cross-sectional and time-series studies of the mortality impacts of airborne particulate matter. Working with a series of talented and dedicated doctoral students and postdoctoral fellows, including Adam Finkel, Neil Hawkins, Alison Cullen, Kim Thompson, Andy Smith, Katy Walker, Scott Wolff, Kevin Brand, George Gray, Sandra Baird, TJ Carrothers and Jouni Tuomisto, Dr. Evans developed approaches for characterizing uncertainty in estimates of environmental health risks and for using such estimates to inform decisions about emissions controls and research prioritization. In the mid-to-late 1990’s Dr. Evans became interested in developing simple and transparent approaches for estimating population exposure to air pollutants. Working with Andy Wilson, Kanchanasak Phonboon and Ying Zhou, he pioneered the development and application of the concept of intake fraction to meet this need. From 2002 until 2008 Dr. Evans directed a program of study to assess the public health impacts of Iraq's 1990 invasion and occupation of Kuwait. The study used epidemiology and risk assessment to characterize the health impacts of mine and ordnance accidents, smoke from the oil well fires, polycyclic aromatic hydrocarbons from the marine and terrestrial oil spills, and depleted uranium from spent munitions.
Keywords: health; nursing